A multi-scale modeling scheme for damage analysis of composite structures based on the High-Fidelity Generalized Method of Cells. (15th December 2018) - Ye, Junjie; Chu, Chenchen; Cai, Heng; Wang, Yongkun; Qiao, Xiaojun; Zhai, Zhi; Chen, Xuefeng
Abstract: This paper presents a description of a multi-scale method to investigate the failure behaviors and damage evolution of composite laminates reinforced with unidirectional fibers. The proposed approach is based on the microscopic mechanical theory and pre-processing function of the ANSYS/LS-DYNA software. At micro-scale, the High-Fidelity Generalized Method of Cells (HFGMC) is employed to establish the microscopic model, which can be used to acquire the microscopic stress distributions in the representative volume element (RVE). Moreover, a viscoplastic constitutive model is employed to describe the nonlinear behaviors of matrix materials. At macro-scale, each integration point in elements is employed to investigate the damage evolution for each lamina. In order to validate the proposed method, the numerical results of failure evolution path and stress-strain responses of the composite laminates are compared with experimental data. A good consistency between theoretical results and experimental data can be found. On this basis, the failure evolution path for each lamina is further investigated. The numerical results revealed that the crack firstly appeared in the 90° lamina. With the further increasing of external loading, the crack will accumulate along with the layer direction for −45° lamina, 45° lamina and 90° lamina.